Анализ заболеваемости спортсменов на современном этапе развития спорта высших достижений - Люгайло, Светлана; Liugailo, Svetlana (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Изучение состояния здоровья спортсменов является актуальной темой в силу того, что показатели соревновательной деятельности напрямую связаны с функциональным состоянием всех систем организма. Анализ данных диспансеризации спортсменов позволил установить, что у 14,50 % была зарегистрирована патология различных органов и систем организма. Нами установлено, что соотношение показателей заболеваемости носит циклический характер и зависит от периода подготовки спортсменов. Анализ структуры патологии у спортсменов позволил определить перспективные направления дальнейшей профилактической деятельности. The study of the health of athletes is an actual theme due to the fact that the performance of competitive activities is directly related to the functional state of all body systems The data analysis of the sportsmen medical examinations allowed to set that pathology of different organs and organism systems was registered in 14,5 % of cases. We established that correlation of morbidity rates has a cyclic character and depends on the period of sportsmen preparation. The conducted analysis of structure of sportsmen pathology allowed to define the perspective directions of further prevention activity.
Analysis of Sportsmen Morbidity on the Modern Phase of Sport Development of Higher Achievements
Keywords: заболеваемость; диспансеризация; спортсмены; профилактика; morbidity; medical examination; sportsmen; prevention activity